2016
DOI: 10.1111/tra.12379
|View full text |Cite
|
Sign up to set email alerts
|

Sorting Nexin 11 Regulates Lysosomal Degradation of Plasma Membrane TRPV3

Abstract: The trafficking of ion channels to/from the plasma membrane is considered an important mechanism for cellular activity and an interesting approach for disease therapies. The transient receptor potential vanilloid 3 (TRPV3) ion channel is widely expressed in skin keratinocytes, and its trafficking mechanism to/from the plasma membrane is unknown. Here, trafficking from the plasma membrane to lysosomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 56 publications
3
13
0
Order By: Relevance
“…Moreover, the abundance of this pathway increased at 35 °C and 40 °C, indicating that the membrane transport metabolism will be enhanced at high temperature. A previous study revealed that there was an important mechanism responsible for temperature sensing in organisms that controls the vesicular transportation of temperature sensory receptors to adjust the transduction of temperature information, which may be an important means of adapting to the variations in environmental temperature [ 67 ]. Overall, the proportion associated with metabolism was highest, and the abundances of other functional pathways varied with temperature, despite being a few differences among some functional pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the abundance of this pathway increased at 35 °C and 40 °C, indicating that the membrane transport metabolism will be enhanced at high temperature. A previous study revealed that there was an important mechanism responsible for temperature sensing in organisms that controls the vesicular transportation of temperature sensory receptors to adjust the transduction of temperature information, which may be an important means of adapting to the variations in environmental temperature [ 67 ]. Overall, the proportion associated with metabolism was highest, and the abundances of other functional pathways varied with temperature, despite being a few differences among some functional pathways.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a report suggest that TRPV3 interacts with Nexin 11, a lysosomal protein. 35 TRPML members belong to TRP superfamily are also present in the lysosome and late endosomes; and defects in these TRPMLs also result in lysosomal storage disorders leading to impaired trafficking of lipids and proteins. 36 Similarly, using patch clamp method, presence of TRPV2 in the endosome has also been confirmed.…”
Section: Discussionmentioning
confidence: 99%
“…Little is known about SNX11; it belongs to a family of retrograde transport molecules, 31 and its protein is involved in targeting cell-surface molecules to the lysosome. 32 CBX1 is a member of the highly conserved heterochromatin protein family that binds to histones through methylated lysine residues, mediating gene silencing and alternative splicing. 33,34 It is believed that CBX1 can play an important role in epigenetic regulation and gene expression.…”
Section: Identification Of Expression Quantitative Trait Locimentioning
confidence: 99%